Reversible thyrotoxic cardiomyopathy: a case report - Aggarwal, Rashmi; Chugh, Pradeep; Sudha, Vipin Vasavan (International Journal of Scientific Reports, 2019)
Hyperthyroidism significantly affects the hemodynamics of the cardiovascular system. It is associated with development of atrial fibrillation, high output cardiac failure, pulmonary hypertension and dilated cardiomyopathy (DCM). In this paper we report a case of thyrotoxicosis induced cardiomyopathy. She was a 54 year old woman who presented with cardiomegaly (dilatation of all four chambers of the heart) secondary to Graves’ disease. She was treated with anti-thyroid drugs, β Blockers and diuretic and her euthyroid status was restored in 6 weeks. A repeat echocardiogram done at this point of time showed normal cardiac function with normalization of ejection fraction. So this was a case of reversible thyrotoxic cardiomyopathy.